EFFICACY AND SAFETY OF MICROPULSE TRANSSCLERAL DIODE LASER CYCLOPHOTOCOAGULATION IN ABSOLUTE GLAUCOMA (Vietnam Journal of Community Medicine, 2022)
Purposess: To evaluate the effectiveness of lowering intraocular pressure and the safety of Micropulse Transscleral diode laser cyclophotocoagulation (MP-TSCPC) with a duty cycle of 31,3% in absolute glaucoma patients.Methods: A prospective interventional study was performed on 64 eyes from October 2020 to April 2021 at the Ho Chi Minh City Eye Hospital.Results: Sixty four patients including 26 females and 38 males were recruited with the mean age 56.1±2.1. The mean IOP at pre- and post-opereration was 45.9±11.0 and 25.8±13.8mmHg, respectively. The average IOP reduced 42.4%, 33.5%, 39.1% and 45.5% from baseline after surgery at 1 week, 1 month, 3 months and 6 months (p value
Keywords: Glaucoma, Micropulse transcleral cyclophotocoagulation.